PENGARUH KEMAMPUAN BERINOVASI, KEMAMPUAN DIGITAL MARKETING, DAN PANDEMI COVID-19 TERHADAP NEW PRODUK DEVEPLOMENT PADA UMKM BIDANG MINUMAN DI PONOROGO - Alberta Adinata; Adi Santoso; Sri Hartono (Jurnal AKTUAL, 2022)
This study aims to find out: 1) To find out how the ability to innovate, digital marketing capabilities and the covid-19 pandemic is carried out by MSME beverage brands in Bangunsari Ponorogo Village in the development of new products: 2) To find out what factors are the obstacles to MSME beverage brands in Kelurahan Bangunsari Ponorogo in carrying out new product development activities. This research uses quantitative research methods. The type of research used by this researcher is a type of quantitative research, namely research that is systematic scientific research on parts and phenomena and the causality of their relationships to avoid an unlimited scope. The subjects used in this study as respondents were MSME brand drinks in Bangunsari Ponorogo Village. The results of this study indicate that: 1) the ability to innovate as seen from the various new product developments in the UMKM beverage brand in Bangunsari Ponorogo Village can be said to be running well. 2) The process of digital marketing capabilities seen from the research results is seen to be still very good and masters all things digital. 3) the covid-19 pandemic on this variable does not affect the development of new products for the beverage brand UMKM in Bangunsari Ponorogo Village.